Stimulation of postprandial in vivo glycogenesis and lipogenesis of rats fed high fructose diet with varied phosphate content - Mattar, Lama E. (2010)
It has been reported that increased fructose intake is associated with the development of the metabolic syndrome. The phosphate (P) sequestering capacity of fructose is likely to affect the phosphorylation capacity of different metabolites, and this, in turn, may be the basis for several metabolic derangements, especially in the P requiring reactions, for example, glycogenesis and lipogenesis. We hypothesized that P enrichment of the diet can balance P status and, consequently, affect glycogenesis and lipogenesis. An animal experiment was executed in which adult male Sprague-Dawley rats were maintained for 4 days on high-fructose diets with different P content (0.15%, 0.165%, 0.30%, and 1.65%). At the end of the feeding period, overnight fasted rats were tube fed a test meal, injected with 3H2O and euthanized 1 hour later. Final plasma glucose, insulin, uric acid, and triacylglycerol concentrations, as well as in vivo rates of glycogen and lipid synthesis and hepatic glycogen content, were measured. Results showed that increased P content of the diet was associated with an increase in postprandial epididymal fat pad (P = .007) and hepatic lipogenesis (P = .029), as well as glycogenesis (P = .024). In conclusion, P content of the diet was found to stimulate both glycogenesis and lipogenesis. These alterations in carbohydrate and fat metabolism point to the potential of P in influencing nutritional status.